Worker participation: a ‘burden’ on the European Company (SE)? - A critical assessment of an EU consultation process - Conference reader 24 and 25 November 2010 - Cremers, Jan; Kluge, Norbert; Stollt, Michael (Brussels, 2010)
"In March 2010, the EU Commission finally made available the so-called ‘Ernst and Young study’ on the operation and the impacts of the Statute for a European Company. Shortly afterwards the Commission launched an online consultation on the results of the study. In July 2010, the European Commission produced a summary report on the replies to the online consultation.This ETUI paper brings together a critical analysis of the consultation procedure, the Commission consultation summary and the ETUI’s reply to the consultation on the Ernst&Young study.